Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-44064-y
|View full text |Cite
|
Sign up to set email alerts
|

GC-Recomposition-Olfactometry (GC-R) and multivariate study of three terpenoid compounds in the aroma profile of Angostura bitters

Abstract: Foods and beverage aroma results from multicomponent mixtures of volatile compounds present in the food that interact with olfactory receptors and produce a perceptual response in the brain. However, the perceptual interactions that occur when complex odor mixtures are combined are not well understood. Here we used Gas chromatography-Recomposition-Olfactometry (GC-R) to better understand the role that individual compounds have on the perceived sensory aroma of bitters. Bitters are the concentrated alcoholic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Linalool has been found to mask aromas when in combination with other terpenes. 42 Perception of monoterpenes in matrix 3 are closest to what can be expected in wines, as it is very similar with both nonvolatile and volatile compositions.…”
Section: ■ Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Linalool has been found to mask aromas when in combination with other terpenes. 42 Perception of monoterpenes in matrix 3 are closest to what can be expected in wines, as it is very similar with both nonvolatile and volatile compositions.…”
Section: ■ Discussionmentioning
confidence: 54%
“…Linalool also appeared to mask the perception of compounds found in profile 4 as this was the main difference between monoterpenes in profile 3 versus profile 4. Linalool has been found to mask aromas when in combination with other terpenes . Perception of monoterpenes in matrix 3 are closest to what can be expected in wines, as it is very similar with both nonvolatile and volatile compositions.…”
Section: Discussionmentioning
confidence: 79%
“…It has been suggested that GC-R-O is capable of the in-instrument perceptually analysis of compounds occurring in the sample, even if they are below their odor threshold, instrumentally undetectable, or without reference standards (Johnson et al, 2012). However, GC-R-O has been applied only in studies of perceptual interactions (Johnson et al, 2012(Johnson et al, , 2019 but not yet demonstrated its potential for identifying unknown volatile components. may also be considered for the purpose of identification, although these techniques have been more focused on perceptual interactions during postidentification.…”
Section: Consideration Of Perceptual Interaction Phenomena For Identifying Wine Volatilesmentioning
confidence: 99%
“…Subsequent GC-MS analysis on these fractions may potentially reveal new candidate volatile compounds that have an indirect aroma impact. Another method for performing perceptual interaction studies is to use GC recomposition-olfactometry (GC-R-O) (Johnson et al, 2012(Johnson et al, , 2019. As indicated by its name, this technique enables the highly automated fractionation (through GC separation and Deans switch), recombination (cryogenic trapping of selected volatiles), and sensory evaluation (olfactometry) in one instrument (Figure 13b).…”
Section: Consideration Of Perceptual Interaction Phenomena For Identi...mentioning
confidence: 99%
“…Monoterpenes were found to influence fruity aromas (orange flowers) in wine, suggesting that linalool (odor threshold of 6 µg/L) [34] and linalool oxide may interact with non-volatiles, resulting in change in their aroma perception [33,35].…”
Section: Free Volatile Aroma Compounds In Fresh and Dehydrated Grapesmentioning
confidence: 99%